Knowledge, Attitude and Practice among endodontists of Nepal in patient management during COVID-19 arena - Kunwar, Deepa; Subham, Snigdha; Nepal, Manisha; Khadka, Jwolan (Journal of Gandaki Medical College-Nepal, 2021)
Background: Coronavirus disease, 2019 (COVID-19) is an infectious disease caused by the severe acute respiratorysyndrome coronavirus 2 (SARS-CoV-2).COVID-19 is a global pandemic affecting all aspects of life in all countries. Endodontist are at inherent risk because of aerosol generating procedures. The objective of the study was to assess the knowledge, attitude and practice (KAP) among Endodontists of Nepal to combat the COVID 19 pandemic. Method:A web-based cross-sectional study was conducted among Endodontist of Nepal from March to June 2021.Convenient sampling method was adopted. The data were analysed using SPSS version 20.Descriptive statistics was performed, percentage and frequency distribution were assessed. Chi-square tests wereused to see the association between the categorical variables. A p-value of <0.05 was considered statistically significant. Results: Out of the total 81 Endodontists who responded to our study, 55.6% of them were females and 44.4% males. Around 65%were from Bagmati province.Majority (87.7%) of responders reported that they categorize the cases on the basis risk assessment, 56.8% do not perform routine procedures during the pandemic. Maximum (97.5%) of the responders discuss about COVID-19 with the patients.About 55% of the responders use rubber dam during the endodontic procedures, while 17.3% of the responders do not use them at all. Conclusion:Endodontists of Nepal werefound to have good knowledge, attitude and practice score, which is important to overcome the present pandemic scenario of COVID19.Certain pitfalls in attitude and practice level can be decreased by efficient training programs, precise guidelines, and treatment protocols.